PENGARUH KUALITAS SISTEM DAN KUALITAS INFORMASI TERHADAP KEPUASAN PENGGUNA SISTEM INFORMASI AKUNTANSI PADA PT INDOMARCO PRISMATAMA CABANG BANJARMASIN - Ruslinda Agustina; Rara Gustiana; Octafia Amini (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2021)
Abstract, The research objective is to empirically prove the effect of system quality and information quality on user satisfaction of accounting information systems at PT Indomarco Prismatama Banjarmasin Branch. The method used in this research is a survey method by distributing questionnaires to employees as respondents as many as 60 people. The test equipment used in this research is with the help of the SPSS version 22 program. Conclusion partially and simultaneously the variables of system quality and information quality have an effect on user satisfaction of the accounting information system at PT Indomarco Prismatama Banjarmasin Branch, this is because employees are satisfied with the accounting information system used by the company.